Disciplinary Penalties for Civil Servants - STOICU, Narcisa Mihaela; MURGU, Simeon; MOROȘTEȘ, Anca Florina (Journal of Legal Studies, 2014)
Disciplinary liability consists of a set of legal rules which penalize disciplinary violation, namely the act, in relation to one’s work, which consists of a culpable act or omission committed by the employee. The trigger of disciplinary liability is the culpable breach of service obligations by the employee. The disciplinary liability of civil servants is governed by Law no. 188/1999 on the status of civil servants. The culpable violation by civil servants of duties pertaining to public office they hold and of the rules of professional and civic conduct provided by law constitutes disciplinary violation and shall result in their being disciplinarily liable. Disciplinary liability has a threefold function, namely punitive, preventive and educational. The Statute of the Civil Service governs the general regime of legal relations between civil servants and the state or local government, through autonomous administrative authorities or the public authorities and institutions of central and local public administration, hereinafter referred to as service relations. The purpose of law is to ensure, in accordance with the legal provisions, a stable, professional, transparent, efficient and impartial public service, in the interests of citizens, as well as the authorities and public institutions of central and local public administration. The culpable violation by civil servants of duties pertaining to public office they hold and of the rules of professional and civic conduct provided by law constitutes disciplinary violation and shall result in their being disciplinarily liable. When establishing the disciplinary penalty, due consideration will be given to the causes and severity of the disciplinary violation, the circumstances in which it was committed, the degree of guilt and consequences of violation, the general behavior of the civil servant during service, and the existence of other disciplinary penalties in his background, which have not radiated under the law.